Promoting The Driving of Community Actvities to Keep Surrounding with Buddhist Principles: A Case Study of Wat Cham Uthit Community, Mueang District, Songhla Province - Chaichanyut, Phrakhrusamu Supphachai; Bowonchaiwat, Phrakhru Bowonchaiwat (Journal of Dhamma for Life, 2025)
This research article aims to: (1) to study theoretical concepts for driving the activities of the Community-Based Treatment (CBTx) model, (2) to explore appropriate Buddhist principles for such initiatives, and (3) to promote the implementation of community-based activities through Buddhist teachings. The case study area was Wat Chaem Uthit Community, which has been experiencing ongoing problems with drug abuse, especially among youth and local residents in high-risk areas such as alleyways and mountainous zones. These conditions have led to compounded issues involving health, education, and family relationships. The research findings revealed that: The findings revealed that the success of the CBTx initiative depended on strong collaboration among three main sectors: local monastics, community leaders, and government-affiliated networks. The activities used to support drug rehabilitation spanned across individual, family, and community levels. These included spiritual-based programs such as novice ordination, moral training camps, and Dhamma discussions; family-based therapies such as home visits by monks and community leaders; and community-based activities such as candlelight processions, tree-planting, and public forums. All initiatives were carried out under the ช conceptual framework of the Four Noble Truths recognizing suffering, understanding its causes, realizing its cessation, and following the path leading to its end. Furthermore, the application of the Four Noble Truths as a framework for rehabilitation yielded highly positive outcomes, especially in the transformation of behavior, mindset, and attitudes among participating patients. Participants gained awareness of life’s value, set occupational goals, and successfully reintegrated into society with dignity. These activities also strengthened community solidarity, making the prevention of drug problems more tangible and sustainable. The model serves as a practical and effective example that can be expanded to other communities.